2015
DOI: 10.1111/obr.12343
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and discrimination – a systematic review and meta‐analysis of observational studies

Abstract: The results provide evidence that perceptions of weight discrimination by individuals with obesity were common, and its negative consequences are highly relevant issues within society and need to be the focus of potential interventions. © 2015 World Obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
223
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(268 citation statements)
references
References 38 publications
15
223
3
15
Order By: Relevance
“…Interestingly, the forum posters in our study wrote relatively little about perceived stigmatisation, although it is inherent in statements such as "wanting life as a fatty to end". Many previous studies have demonstrated the extensive and deep-reaching stigmatisation of people with morbid obesity in all social arenas, including healthcare [28].The findings of the present study show that the attainment of this "new life" did not come easily. Rather, the posters' posts on the discussion forum showed an intricate process of negotiation with the healthcare system.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…Interestingly, the forum posters in our study wrote relatively little about perceived stigmatisation, although it is inherent in statements such as "wanting life as a fatty to end". Many previous studies have demonstrated the extensive and deep-reaching stigmatisation of people with morbid obesity in all social arenas, including healthcare [28].The findings of the present study show that the attainment of this "new life" did not come easily. Rather, the posters' posts on the discussion forum showed an intricate process of negotiation with the healthcare system.…”
contrasting
confidence: 48%
“…Interestingly, the forum posters in our study wrote relatively little about perceived stigmatisation, although it is inherent in statements such as "wanting life as a fatty to end". Many previous studies have demonstrated the extensive and deep-reaching stigmatisation of people with morbid obesity in all social arenas, including healthcare [28].…”
Section: Discussionmentioning
confidence: 99%
“…En un entorno obeso-génico como el de nuestra sociedad actual, donde existe un fácil acceso a los alimentos y donde muchos de estos están altamente procesados, viendo mejoradas sus capacidades sensoriales, la persona con obesidad se ve abocado a una lucha fútil. A pesar de ser una víctima, es criminalizada en su condición, achacándose a su falta de fuerza voluntad o irresponsabilidad, incluso por los propios profesionales sanitarios [65][66][67][68] . CONCLUSIONES Con las proporciones pandémicas alcanzada por la prevalencia de la obesidad, es crucial ser conscientes de los factores que impulsan el riesgo de enfermedad crónica en pacientes con sobrepeso/obesidad.…”
Section: Figura 3 Expansión Del Tejido Adiposo (Adaptado Deunclassified
“…On the other side of the coin, the consequences of obesity are clear: fewer and lower-quality job opportunities, lower wages (especially for women) (5) and higher costs of health care (especially those arising from morbid obesity, BMI>35). These negative outcomes on society justify government intervention.…”
Section: On Obesitymentioning
confidence: 99%